Structural pavement project. Characterization of the dynamic modulus of asphalt mixtures for mechanistic-empirical pavement design - Romero, Pedro (2025)
The new structural pavement design method based on mechanistic-empirical principles was recently developed in the United States through NCHRP Project 1-37A (Development of Mechanistic-Empirical Pavement Design). This method requires new types of testing for mixture characterization, such as dynamic modulus testing and indirect tensile strength, as well as detailed traffic and climate data. Due to the novelty of the method, the need for new testing equipment, and the users’ lack of familiarity with the procedure, the method has not yet been officially adopted. To date, very few pavements have been designed using this new approach. This study documents one of the first efforts to incorporate the required testing protocols for structural pavement design using the new mechanistic-empirical program. The dynamic modulus of two 19-millimeter asphalt mixtures was determined using the tests proposed in NCHRP Report 465: Simple Performance Tests for Asphalt Mixtures (SPT). One of the mixtures was prepared with unmodified PG 64-28 asphalt, while the other was made with PG 58-34 asphalt modified with 25% TLA (Trinidad Lake Asphalt). Using the results from the SPT and the Superpave volumetric properties, the mechanistic-empirical pavement design method was applied to predict pavement performance under typical Utah conditions over a 20-year period. Based on the results of this study, the economic benefits of asphalt modification were evaluated in terms of pavement lifespan under given traffic and climate scenarios. This lifespan was based on specific types of pavement distress, such as permanent deformation (rutting), thermal cracking, and others. With these new methods, highway agencies can more easily determine whether the additional cost of asphalt modification is justified based on the expected performance of the pavement. The adoption of the new mechanistic-empirical design system is recommended.